Sentidos atribuídos pelos alunos do I Ciclo de Ensino Secundário às práticas do recreio da Escola do Cabassango II em Cabinda- Angola - Celso Chipi Uzana Jose (2014)
The purpose of this study is to verify what students think and what they do in time for the playground/school break and that way this time/space relates to the set of activities developed at school. Among the goals outlined, sought to map and identify the practices carried out in the free time and what are the senses and meanings assigned to them by the students. This study sought to investigate the playground, understanding it as a social practice, within the context of the second educational reform in Angola, which has as its motto the development of a quality school for all. The investigation had as theoretical-methodological assumption the historical-cultural Approach of Vygotsky (1934-1987) articulated with the perspective of situated Learning Lave and Wenger (1991) and Lave (1990) who understands human beings as essentially social and building their learnings immersed in concrete social practices. This work is limited in the field of qualitative research and the quest for understanding of the senses and meanings that the subjects teens attributed to free time at school. To understand the phenomenon researched was required a systematic study of the educational history of Angola, as well as an immersion into the field. The data were collected through interviews and video recordings of the daily life of the school. With the analysis of the data it was possible to obtain evidence that: (a) the existence or not of the school playground is controversial when it examines the official documents, the speeches of leaders of schools and the Organization of the times; (b) the relationship that students and teachers establish with time lived at school is totally different to that established in the official documents; (c) the meanings assigned by students to free time experienced at school makes emerge another school within the school; (d) the implementation of educational reform in the Angolan education system, is in the process of consolidation, demand adequate infrastructure and resources available. To investigate the practice Cabinda school playground we encounter problems historically constituted that demand solutions within the framework of educational policies that establish principles of hygiene, health, safety in the school environment, to a country in the process of construction.